Implementasi Total Quality Management Bidang Akademik dan Sarana Prasarana di SMA Negeri 1 Sidoarjo - Widyanti, Hanny (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2017)
This study focused on issues such as: (1) the standard setting process of quality assurance academic field; (2) The standard-setting process of quality assurance field of infrastructure; (3) the socialization process of the implementation of academic quality assurance; (4) the socialization process quality assurance infrastructure; (5) monitoring and evaluation of the quality standards of academic fields in SMAN 1 Sidoarjo by the principal; (6) the process of monitoring and evaluation of quality standards in the field of infrastructure SMAN 1 Sidoarjo by principalsThis study is using a qualitative approach and descriptive and case study. Through data collection techniques based on participant observation, interviews, and documentation. The subjects in this study consists of the principal, vice principal infrastructure (team leader of school development), vice principal curriculum, teachers, staff, school committees and parents. The data were tested with the technique of credibility, dependability, and confirmability.Keywords:Â  Total Quality Management, academic, infrastructure.